Struggle of child based Co-curricular Educational Institutions in the post-pandemic era from the perspective of Aloha Bangladesh; online education in Bangladesh - Hridi, Farha Shams (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.